2003
DOI: 10.1242/dev.00506
|View full text |Cite
|
Sign up to set email alerts
|

Ogon/Secreted Frizzled functions as a negative feedback regulator of Bmp signaling

Abstract: The zebrafish mutant ogon (also called mercedes and short tail) displays ventralized phenotypes similar to the chordino (dino) mutant, in which the gene for the Bmp antagonist Chordin is mutated. We isolated the gene responsible for ogon by a positional cloning strategy and found that the ogon locus encodes a zebrafish homolog of Secreted Frizzled(Sizzled), which has sequence similarity to a Wnt receptor, Frizzled. Unlike other secreted Frizzled-related proteins (sFrps) and the Wnt inhibitor Dickkopf1, the mis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
143
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(153 citation statements)
references
References 59 publications
9
143
0
1
Order By: Relevance
“…Noggin, follistatin, and chordin, the first neural inducers that were identified (Hemmati-Brivanlou et al 1994;Sasai et al 1994Sasai et al , 1995, act by suppressing BMP signaling (Piccolo et al 1996;Zimmerman et al 1996;Fainsod et al 1997). Additional BMP antagonists secreted from the organizer include Cerberus, Gremlin, Dan, Drm, Coco, and Ogon/Sizzled (sFRP) (Wagner and Mullins 2002;Yabe et al 2003).…”
Section: Neural Inductionmentioning
confidence: 99%
“…Noggin, follistatin, and chordin, the first neural inducers that were identified (Hemmati-Brivanlou et al 1994;Sasai et al 1994Sasai et al , 1995, act by suppressing BMP signaling (Piccolo et al 1996;Zimmerman et al 1996;Fainsod et al 1997). Additional BMP antagonists secreted from the organizer include Cerberus, Gremlin, Dan, Drm, Coco, and Ogon/Sizzled (sFRP) (Wagner and Mullins 2002;Yabe et al 2003).…”
Section: Neural Inductionmentioning
confidence: 99%
“…Sizzled, a secreted frizzled-related protein (sFRP) originally described as a Wnt signaling antagonist, has surprisingly been identified as the product of the ogon/mercedes locus, that acts as an inhibitor of BMP signaling in zebrafish dorsal-ventral patterning (Martyn and SchulteMerker, 2003;Yabe et al, 2003). It has recently been shown that Xenopus and zebrafish Sizzled can act by binding BMP1/TLD-like proteinases and inhibiting their chordinase activity (Lee et al, 2006) (Fig.…”
Section: Inhibitors Of Bmp1/tld-like Proteinasesmentioning
confidence: 99%
“…1B), consistent with the suggestion that wnt8 loss-of-function embryos do not provide a BMP-permissive environment. szl encodes a feedback inhibitor of BMP, thus its expression is a readout of BMP signaling activity (Martyn and Schulte-Merker, 2003;Yabe et al, 2003). szl is expressed in the ventral embryo before and during gastrulation and in the tailbud and ventral posterior epidermis at bud stage (Yabe et al, 2003).…”
Section: Increased Bmp Antagonism Leads To Reduced Bmp Signaling In Wmentioning
confidence: 99%